How job crafting behaviors influence the innovative behavior of knowledge workers in the gig economy: based on the organismic integration theory - Song, Linpei; Jo, Sung Jun (Frontiers in Psychology, 2023)
Introduction The gig economy is extolled for its potential to stimulate economic and social development. This study examines the mediating roles of controlled and autonomous motivation in the relationship between job crafting and innovative behavior in the context of knowledge workers in the gig economy. Methods To examine these relationships, we propose and test a conceptual framework using an online survey conducted among knowledge workers in China. The participants consisted of 302 knowledge workers who voluntarily participated in the study. We used structural equation modeling to test the proposed relationships among the variables. Results Controlled and autonomous motivation mediates the relationship between job crafting and innovative behavior. Discussion Our study shed light on the knowledge workers’ motivation dilemma in the gig economy, with theoretical implications for research regarding job crafting, motivation, and practice implications about the job crafting and innovative behavior of knowledge workers.